Woma(e)n incarcerated: freedom through expression - Byrne, Sarah Eve (My University, 2010)
Architecture possesses the ability to perform a transformative role in society. The opportunity to explore this ability exists in the prison/ incarceration arena as the problems posed by crime and punishment are part of a larger societal debate, and as such there is the need for a new architectural response. This thesis seeks to propose a new incarceration-hybrid as a means of rehabilitation to alleviate a certain section of the female prisoner demographic, through the medium of art expression and performance as a means to allow prisoners a freedom and exploration of their identities. The thesis will explore the various social factors and structural inequalities that have led women to transgress the law in South Africa, taking into account the oppression of women through, or because of their bodies and loss of identity. Once the subject group has been explained, understood and placed into context, the thesis will move on to examine the notions of space within the existing penal reform system, with a specifi c focus on how the body-mind space is acted on in space and time as a means of institutional control. Once an understanding of how a process of institutional identity is established and how this affects individual identity and the process of rehabilitation, the new hybrid will be theorized in terms of how the facility can counteract the process of identity moulding (or stripping) to replace the process with one of expression and identity exploration underpinned by the rehabilitative theory. An analysis of the potential spaces in the hybrid will also be theorized in terms of how the body-mind space will potentially be acted on in space and time, to show how self expression can be used as a counterpoint to the process of mortifi - cation. This thesis will draw on various theorists and frameworks to discuss notions of body, mind, space and time from diverging angles and how these are used institutionally to control and punish as well as how this is currently expressed architecturally, inhibiting the process of rehabilitation.